2020
DOI: 10.21203/rs.2.21011/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of a Core Outcome Set for Fetal MyelomenIngoCele (COSMiC): study protocol

Abstract: Background: Open spina bifida (OSB) is one of the most common congenital central nervous system defects and leads to long-term physical and cognitive disabilities. Open fetal surgery for OSB improves neurological outcomes and reduces the need for ventriculoperitoneal shunting, compared to postnatal surgery, at the expense of increased prematurity. It however confers significant morbidity to the mother in the index pregnancy and potential risks to future pregnancies. Fetoscopic surgery may prevent maternal morb… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…14,20 Because there are no data to support the idea that being unable to match our postnatal surgery patients to fetal surgery patients for fetal surgery exclusion affected the validity of our findings, we concluded that such matching was not mandatory for our study. This issue could be addressed someday by a consortium of fetal surgery centers using a set of common data elements (now in development 36 ) and following patients prospectively.…”
Section: Discussionmentioning
confidence: 99%
“…14,20 Because there are no data to support the idea that being unable to match our postnatal surgery patients to fetal surgery patients for fetal surgery exclusion affected the validity of our findings, we concluded that such matching was not mandatory for our study. This issue could be addressed someday by a consortium of fetal surgery centers using a set of common data elements (now in development 36 ) and following patients prospectively.…”
Section: Discussionmentioning
confidence: 99%
“…10-14 A study protocol registered in 2020 aims to develop a COS looking specifically at the outcomes of open fetal surgery for open MMC. 15 To date, no COS is available to define the success of interventions in the later management of orthopaedic conditions associated with SD. The standardization of outcomes reporting for studies investigating treatment options will allow meaningful meta-analyses to be made, and will lead to clear guidelines for the orthopaedic management of this condition.…”
Section: Introductionmentioning
confidence: 99%